Análise crítica sobre o dimensionamento ao cisalhamento em vigas de concreto armado segundo a NBR 6118 (2003) - Adriana Bicalho Ribeiro (2005)
The Brazilian code NBR 6118/2003 introduces significant changes in the criteria for the shear strength of reinforced concrete (RC) beams. Two design models are presented and in one of them allowance is given to the designer to vary the inclination of the compressive struts ¦È between 30º and 45º In this scenario, the objective of this work is to evaluate these shear design procedures with respect to experimental results of RC beams, with and without stirrups built with normal (fc < 50MPa) and high-performance (fc > 50MPa). The effects of the transversal and longitudinal reinforcement rates, beam effective depth and concrete compressive concrete strength are investigated in the comparative study. EUROCODE 2/2003 and ACI 318/2005 shear design criteria arealso analyzed. The data basis of experimental results is composed of 522 beams from which 311 have transversal reinforcement. The comparative analysis strongly suggests the revision of NBR 6118 design equation for the concrete contribution in the shear strength of RC beams. The effects of longitudinal reinforcement rate and beam effectivedepth must be explicitly included in the formulation. The overall comparative analysis indicates that NBR 6118 design criteria (model II with ¦È equals to 30º) provides the best correlation with respect to test results in terms of safety, precision and economy of beams with stirrups and concrete compressive strength up to 50 MPa. Poor correlationof these design criteria was, however, obtained for beams with effective depth greater than 60 cm and longitudinal reinforcement rate below 2%.Keywords: reinforced concrete beams, shear, design codes.